SLIT3 promotes myogenic differentiation as a novel therapeutic factor against muscle loss. Issue 6 (22nd August 2021) - Cho, Han Jin; Kim, Hyeonmok; Lee, Young‐Sun; Moon, Sung Ah; Kim, Jin‐Man; Kim, Hanjun; Kim, Min Ji; Yu, Jiyoung; Kim, Kyunggon; Baek, In‐Jeoung; Lee, Seung Hun; Ahn, Kyong Hoon; et al.
Abstract: Background: Sarcopenia and osteoporosis frequently co‐occur in the elderly and have common pathophysiological determinants. Slit guidance ligand 3 (SLIT3) has been recently discovered as a novel therapeutic factor against osteoporosis, and a SLIT3 fragment containing the second leucine‐rich repeat domain (LRRD2) had a therapeutic efficacy against osteoporosis. However, a role of SLIT3 in the skeletal muscle is unknown. Methods: Skeletal muscle mass, strength, and/or physical activity were evaluated in Slit3 −/−, ovariectomized, and aged mice, based on the measurements of muscle weight and grip strength, Kondziella's inverted hanging test, and/or wheel‐running test. Skeletal muscles were also histologically evaluated by haematoxylin and eosin staining and/or immunofluorescence. The ovariectomized and aged mice were intravenously injected with recombinant SLIT3 LRRD2 for 4 weeks. C2C12 cells were used to know cellular effects of SLIT3, such as in vitro myogenesis, fusion, cell viability, and proliferation, and also used to evaluate its molecular mechanisms by immunocytochemistry, immunoprecipitation, western blotting, real‐time PCR, siRNA transfection, and receptor‐ligand binding ELISA. Results: Slit3 ‐deficient mice exhibited decreased skeletal muscle mass, muscle strength, and physical activity. The relative masses of gastrocnemius and soleus were lower in the Slit3 −/− mice (0.580 ± 0.039% and 0.033 ± 0.003%, respectively) than those in the WT littermates (0.622 ± 0.043% and 0.038 ± 0.003%, respectively) (all, P < 0.05). Gastrocnemius of Slit3 −/− mice showed the reduced number of Type I and Type IIa fibres (all, P < 0.05), but not of Type IIb and Type IIx fibres. SLIT3 activated β‐catenin signalling by promoting its release from M‐cadherin, thereby increasing myogenin expression to stimulate myoblast differentiation. In vitro experiments involving ROBO2 expression, knockdown, and interaction with SLIT3 indicated that ROBO2 functions as a SLIT3 receptor to aid myoblast differentiation. SLIT3 LRRD2 dissociated M‐cadherin‐bound β‐catenin and up‐regulated myogenin expression to increase myoblast differentiation, in a manner similar to full‐length SLIT3. Systemic treatment with SLIT3 LRRD2 increased skeletal muscle mass in both ovariectomized and aged mice (all, P < 0.05). The relative masses of gastrocnemius and soleus were higher in the treated aged mice (0.548 ± 0.045% and 0.033 ± 0.005%, respectively) than in the untreated aged mice (0.508 ± 0.016% and 0.028 ± 0.003%, respectively) (all, P < 0.05). SLIT3 LRRD2 treatment increased the hanging duration of the aged mice by approximately 1.7‐fold (P < 0.05). Conclusions: SLIT3 plays a sarcoprotective role by activating β‐catenin signalling. SLIT3 LRRD2 can potentially be used as a therapeutic agent against muscle loss.